IMAGE DISPLAY PROGRAM OPEN APPLICATION USING MICROSOFT VISUAL BASIC VERSION 6.0 - Sumando Parulian Rumahorbo; Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2002)
The use of computers as a tool to solve human problems is felt more and moreincreasing. This is supported by the emergence of a programming language thatsupports OOP techniques (Object Oriented Programming). With the OOP techniqueswill work to make the program easier than ever before. Examples of programminglanguages that have supported this facility from Microsoft Visual Basic.In order to comply with our requests and needs of programmers, Microsoft continuesto update this programming language. At the time of writing the final version ofVisual Basic is Microsoft Visual Basic version 6.0.In this writing, the author uses the Microsoft Visual Basic version 6.0 to create anapplication program for individuals.